2019
DOI: 10.1111/jnc.14639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabinoids in Amyotrophic Lateral Sclerosis (ALS) murine models: a systematic review and meta‐analysis

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder that results from motor neuron damage. Cannabinoids have been proposed as treatments for ALS because of their anti‐excitotoxicity, anti‐oxidant and anti‐inflammatory effects. Preclinical studies in mice models of ALS have been published using a range of cannabinoid formulations and doses. To date, there has been no rigorous evaluation of these trials to assess a potential cannabinoid treatment effect. This review and meta‐analysis was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
(229 reference statements)
0
24
0
2
Order By: Relevance
“…A systematic review of CBs in ALS-murine models29 demonstrated the efficacy of CBs in prolonging survival of SOD1-G93A mice. A high-CBD-low-THC formulation was chosen because this most closely resembles the preparation used in an animal model study30 which demonstrated prolonged survival.…”
Section: Methods and Analysismentioning
confidence: 99%
“…A systematic review of CBs in ALS-murine models29 demonstrated the efficacy of CBs in prolonging survival of SOD1-G93A mice. A high-CBD-low-THC formulation was chosen because this most closely resembles the preparation used in an animal model study30 which demonstrated prolonged survival.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In addition, zinc is also known to perform key functions in various pathological mechanisms traditionally correlated with ALS [220]. Cannabinoids have also been postulated as therapeutic options for ALS owing to their anti-in lammatory, antioxidant, and anti-excitotoxicity properties [221,222]. Cannabinoid sources include lax seeds, hemp oil, seeds, eggs, and anchovies [223].…”
Section: Als and Nutrientsmentioning
confidence: 99%
“…Istnieją także nieobjęte jeszcze badaniami klinicznymi interesujące kierunki poszukiwań skutecznej terapii opisywanej choroby, takie jak wpływ kanabinoidów na stan pacjentów z SLA -ich skuteczność została dobrze opisana na modelu zwierzęcym [7], ale brak jest dowodów na skuteczność ich stosowania u ludzi.…”
Section: Stwardnienie Zanikowe Boczne Jako Problem Terapeutycznyunclassified
“…Jednak zwracając uwagę na charakter choroby, statystykę jej występowania (jest to choroba rzadka) i konieczność unifikacji grupy pod względem parametrów klinicznych oraz dotychczas przeprowadzone doświadczenia, nie są one dyskredytujące. Należy zauważyć, że badanie rejestracyjne leku zawierającego edaravon zostało przeprowadzona na grupie 184 pacjentów, z których 68 przyjmowało badany lek [7]. Zwraca więc uwagę niejednolite podejście badaczy do określenia efektywności leczenia.…”
Section: Badania Kliniczne Nowych Leków W Stwardnieniu Zanikowym Boczunclassified